EFFECTIVENESS IN THE PRODUCTION OF BIOMASS OF THE ESTABLISHED ERVA-MATE WITH PRODUCED SEEDLINGS OF STAKES AND OF SEEDS - PICHETH, José Augusto Teixeira de Freitas (Scientia Agraria, 2002)
The present study, established in the field in December 1989, in Guarapuava-PR, was accomplished seeking to avaluate comparatively, erva-mate plants originated from seedling of rooted cuttings and seeds in field planting conditions. The treatments were designed to have seven repetitions and plants of fifteen useful plants, were established at spacing of 3.0 m by 3.0 m. evaluations were carried out to, from the first up to the fifth year, the variables for: survival, plant height and crown diameter, whereas commercial leaves production evaluation was carried out in the fifth year. In order to determine possible significant differents among the treatments, destructive sampling was conducted in the nineth year, by randon, for determination of: plant height, height and crown diameter, leaves mass weight, green weight of woody material, lenght and the root system, besides the root system green weight. In the evaluations during the first five years, survival was 82,86% and 85,72% for seed germination and rooted cutting respectively. The plant height and the crown diameter did not showed significant differences, thought, after the pruning of formation, in the second year, the increment analysis revealed a distinguished behavior among the treatments. The commercial yield was 2,947 kg of green leaves and 1,214 kg of dry leaves for seed germination, and 2,168 kg of green leaves and 0,841 kg of dry leaves rooted cutting seedling. It represented a significant difference, in the third year after pruning of formation. In the nineth year, four years after crop, the weight evaluation of the leaves mass did not showed significant differences, suggesting a recovery of the rooted cutting seedling treatment. In the same evaluation, it was noticed that: the plant height, the height and crown diameter, the green weight of the woody material (stem and branches), the lenght and diameter of the root system and the green weight of the root system did not showed significant statistical differences. It can be considered that the treatments are similar at this time and for these work conditions. It was evidenced that there are differences in the leaf mass production and these area associated to the different behavior of the anual increments in height and crown diameter; the treatments do not influence in the plant final form, or in the radical system, stem or crown.